Hacking : the next generation - Dhanjani, Nitesh (O'Reilly, 2009)
With the advent of rich Internet applications, the explosion of social media, and the increased use of powerful cloud computing infrastructures, a new generation of attackers has added cunning new techniques to its arsenal. For anyone involved in defending an application or a network of systems, Hacking: The Next Generation is one of the few books to identify a variety of emerging attack vectors. You'll not only find valuable information on new hacks that attempt to exploit technical flaws, you'll also learn how attackers take advantage of individuals via social networking sites, and abuse vul.